Implicit attitudes and implicit prejudices. (17th August 2016) - Baston, René; Vosgerau, Gottfried
Abstract: In social psychology, the concept of implicit attitudes has given rise to ongoing discussions that are rather philosophical. The aim of this paper is to discuss the status of implicit prejudices from a philosophical point of view. Since implicit prejudices are a special case of implicit attitudes, the discussion will be framed by a short discussion of the most central aspects concerning implicit attitudes and indirect measures. In particular, the ontological conclusions that are implied by different conceptions of implicit attitudes will be scrutinized. The main question to be discussed involves whether implicit prejudices are mental states at all, or whether they are (despite the label 'implicit mental states') rather dispositions to behave in a certain way. This question will be discussed against the background of principles for belief (and mental state) ascription, which requires ascribed mental states to fulfill some specific explanatory role. We defend a conception of implicit prejudices that does not assume them to be mental states.